Learning through citizen science : enhancing opportunities by design - Pandya, Rajul; Dibner, Kenne A. (The National Academies Press, 2018)
"[This book] discusses the potential of citizen science to support science learning and offers insight into how citizen science projects might be designed to achieve specific science learning outcomes. This report also lays out a research agenda that can fill gaps in the current understanding of how citizen science can support science learning and enhance science education" --
"Committee on Designing Citizen Science to Support Science Learning, Board of Science Education, Division of Behavioral and Social Sciences and Education"
"A consensus study report of The National Academy of Sciences, Engineering, Medicine"
Keywords: věda -- sociální aspekty; věda -- učení; vědecký výzkum; veřejnost; spolupráce; science -- social aspects; science -- learning; scientific research; public sphere; cooperation; kolektivní monografie; collective monographs